Lightpath restoration in WDM optical networks. - Mohan, G.
Optical networks employing wavelength-division multiplexing and wavelength routing are potential candidates for future wide area networks. Because these networks are prone to component failures and carry a large volume of traffic, maintaining a high level of service availability is an important issue. This article discusses providing tolerance capability to the optical layer in WDM-based transport networks. It presents a survey on restoration schemes available in the literature, explains the operation of these schemes, and discusses their performance.
Keywords: WDM optical networks; WDM-based transport networks; Component failures; Distributed control protocol; Lightpath restoration; Multiplexing based routing; Network design; Network performance; Optical layer; Restoration schemes; Service availability; Tolerance capability; Traffic; Wavelength routing; Wavelength-division multiplexing; Wide area networks